2019
DOI: 10.1016/j.euroecorev.2018.12.006
|View full text |Cite
|
Sign up to set email alerts
|

On the merit of equal pay: Performance manipulation and incentive setting

Abstract: Work performance is often difficult to assess thus leaving room for manipulation of commonly-used metrics. We created a laboratory workplace in which we can precisely assess both work performance along with manipulation activities. Using two independent experiments we show that, whenever pay for performance is used, manipulation is pervasive leading to both a waste of organizational resources and a weakening of incentives. By contrast, paying organizational members equally effectively deters manipulation attem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 106 publications
0
3
0
Order By: Relevance
“…However, Corgnet et al. (2019, p.23) state that ‘Because presenting oneself in a positive light will typically bring monetary benefits, organizational members are likely to engage in “window‐dressing” activities so as to appear as high contributors. These window‐dressing activities consist in making one's contribution appear deceptively favorable’.…”
Section: Theoretical Framework and Research Hypothesesmentioning
confidence: 99%
“…However, Corgnet et al. (2019, p.23) state that ‘Because presenting oneself in a positive light will typically bring monetary benefits, organizational members are likely to engage in “window‐dressing” activities so as to appear as high contributors. These window‐dressing activities consist in making one's contribution appear deceptively favorable’.…”
Section: Theoretical Framework and Research Hypothesesmentioning
confidence: 99%
“…Anecdotal evidence documents that, under competitive incentives, employees cut corners to meet their targets and get promotions (Gellene, 1992;Greenwald, 2001;Zoltners et al, 2016), allocate their time to window-dressing instead of productive activities (Mitchell et al, 2018;Corgnet et al, 2019), or even commit outright fraud (Association of Certified Fraud Examiners, 2020). Likewise, experimental findings document that competition is associated with a higher degree of misconduct compared to individual payment schemes (Carpenter et al, 2010;Faravelli et al, 2015;Benistant et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In the organizational domain, the relationships between CR and job performance and training proficiency have also been studied. However, the empirical studies offer a variety of results, some of them showing no relationship between CR and job performance (e.g., Lado et al, 2021) and others showing a moderate correlation (e.g., Corgnet et al, 2015bCorgnet et al, , 2019Otero, 2019;. Research on the relationship between CR and training proficiency also offers an optimistic view, as many studies reported that CR was a relevant predictor of this criterion, although there was also observed variability in the estimates of the relationship (Toplak et al, 2014;Gómez-Veiga et al, 2018;Otero, 2019;Muñoz-Murillo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%